Probing the ethics of Holocaust culture - Fogu, Claudio 1963-; Kansteiner, Wulf 1964-; Presner, Todd Samuel (Harvard University Press, 2016)
Probing the Ethics of Holocaust Culture interrogates the memorial cultures, forms of representation, and emblematic debates that have shaped the field of Holocaust studies over the last twenty-five years. It brings together academics of the eyewitness generation with a new generation of academics, authors, and artists who have challenged the "limits of representation" through their scholarly and cultural practices. These practices span the analogic media of history, literature, and film as well as the nonanalogic world of architecture, digital archives, and geographic information systems. Organized around three interlocking themes...the stakes of narrative, the remediation of the archive, and the politics of exceptionality...the purpose of the book is to investigate the complex question of ethics at the heart of global Holocaust culture and, more broadly, genocide remembrance. Explicitly building upon the debates of the 1990s encapsulated in Probing the Limits of Representation, the present volume probes the ethics of Holocaust culture by focusing on the public memorial cultures, institutional formations, and artifacts of cultural memory and history generated by Holocaust remembrance. The essays in this volume take stock of and critically analyze the practices of representation, the remediation of archives, and the comparative, even relativist, frameworks for confronting (and perhaps unmooring) the uniqueness of the Holocaust....